Employment relations under coalition government: the UK expérience, 2010-2015 (Abingdon, 2016)
"Drawing on a wide range of up-to-date research, Employment Relations under Coalition Government critically examines developments in UK employment relations during the period of Conservative-Liberal Democrat government between 2010 and 2015, against the background of the 2007-08 financial crisis, subsequent economic recession and in the context of the primacy accorded to neo-liberal austerity. Contributions cover a series of important and relevant topics in a rigorous, yet accessible manner: labour market change and the rise of zero-hours contracts and other forms of precarious employment; policy development relating to young people's employment; the coalition's welfare-to-work agenda; its programme of employment law reform and its approach to workplace equality and health and safety; labour migration; the experience of the trade unions under the coalition and their responses; and developments in employment relations in the public services. This book addresses the broader issues relating to the coalition period, such as the implications of political and regulatory change for employment relations, including the greater devolution of powers to Scotland and Wales, and locates UK developments in comparative perspective. The book concludes with an assessment of the prospects for employment relations in the aftermath of the May 2015 Conservatives election victory."